EXPLORING EFL LEARNER AUTONOMY IN THE 2013 CURRICULUM IMPLEMENTATION - Sa'adah Ramadhiyah, - (2018)
The 2013 curriculum in Indonesia expects a change in the teaching and learning process from teacher-centered to be the student-centered learning. In regard to this matter, the students should be trained to be autonomous learners in their learning. Unfortunately, it cannot be denied that learner autonomy still poses a challenge to be implemented in Indonesia since the teacher-centered learning is still dominant. That is why it is important to explore the perceptions of both Indonesian teacher and the students in one study to see in-depth information of their perceptions of learner autonomy and the teacher's efforts to promote it in EFL classroom. By employing a case study, this study used the interview, observation and questionnaire as the principal data collection methods. An English teacher and thirty six students from twelve grade of one senior high school in Indonesia were involved to elicit their perceptions on learner autonomy and how the teacher's efforts in promoting learner autonomy in the 2013 curriculum. The findings showed that the teacher understood the basic features of learner autonomy as learners' independent learning activity outside the classroom. This study also underlined that the teacher has had initiative to promote learner autonomy in the 2013 curriculum implementation by doing some efforts. However, the teacher has not yet provided the learning process with a wide variety of authentic materials. In this study, learners' perspectives were categorized into technical, psychological and political perspectives (Benson, 1997). It was found that the learners' attitude toward those three perspectives on learner autonomy did not indicate the students to be autonomous learners because they were still accustomed with the teacher-centered learning environment. The research findings revealed that both the teacher's perspective and the learners' perspectives on learner autonomy still needs to be developed for the better learner autonomy application in the 2013 curriculum implementation. ;---Kurikulum 2013 di Indonesia mengharapkan perubahan pada proses belajar mengajar dari teacher-centered menjadi learner-centered. Berkaitan dengan permasalahan itu, siswa seharusnya dilatih untuk menjadi lebih aktif dalam proses belajar mengajar. Sayangnya, tidak bisa dipungkiri bahwa learner autonomy ini masih sulit untuk diterapkan dalam proses belajar mengajar di Indonesia karna teacher-centered masih dominan. Oleh sebab itu, ini menjadi penting untuk mengeksplor persepsi antara guru dan siswa terhadap learner autonomy ini dalam satu penelitian untuk mendapatkan informasi yang mendalam terkait tentang persepsi mereka dan bagaimana guru berusaha untuk mempromosikan learner autonomy ini di dalam kelas. Dengan menggunakan metode penelitian studi kasus, penelitian ini menggunakan interview, observasi dan angket sebagai instrumen untuk mengumpulkan data. Seorang guru bahasa inggris dan 36 siswa dari kelas 12 ikut berpartisipasi dalam penelitian ini. Hasil penelitian menunjukkan bahwa guru sudah memahami konsep standar dari learner autonomy yaitu kemandirian siswa dalam belajar khususnya diluar kelas. Penelitian ini juga menemukan bahwa guru sudah mulai mempromosikan learner autonomy di dalam kelas dengan melakukan beberapa cara. Tetapi, guru belum menyediakan materi yang bervariasi dalam proses belajar mengajar. Sementara itu, persepsi siswa yang didalam penelitian ini meliputi technical perspective, psychological perspectives, political perspectives (Benson, 1997), menunjukkan bahwa ketiga persepsi mereka ini belum bisa mengindikasikan bahwa mereka autonomous learners. Ini dikarenakan mereka masis terbiasa dengan pembelajaran teacher-centered. Berdasar hasil penelitian, persepsi guru dan siswa terhadap learner autonomy masih perlu dikembangkan agar implementasinya dalam kurikulum 2013 menjadi lebih baik.